Estimativa de herdabilidade em geração F₂ w F₃ de inverno em soja - Machado dos Santos, Vera Lúcia; Sigueyuki Sediyama, Carlos; Sediyama, Tuneo; Floriano de Moraes, Carlos (Revista Ceres, 2025)
Broad sense heritability of some soybean characteristics was estimated on the basis of F2 and F3 populations of ‘Parand’ x ‘UFV-1’ cross. Both generations were grown in Vigosa, State of Minas Gerais, located at 650 m altitude, 20°45’S latitude and 42°51’W longitude. The F2 was grown in the summer of 1979/80 and the F3 in the winter of 1980.